Trust as the Foundation of Economic Interaction in Local Communities - Sri Niar Rahayu; Kaisa Nafi Ghassani; Muhammad Aqil Akmal Asqolani; Sri Damayanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Economic interactions within local communities often face challenges such as uncertainty and high transaction costs when relying solely on rigid formal market rationality. This research is crucial as it examines how trust functions as an essential social infrastructure to maintain economic stability and efficiency at the grassroots level. The objective of this study is to analyze the transformation of trust as social capital that drives the economic wheel of local communities in Indonesia. The research method employed is a qualitative approach using the library research method. Data were collected through a comprehensive literature search of scientific journals, books, and research reports, which were then analyzed using content and thematic analysis techniques within the framework of embeddedness theory. The results indicate that trust significantly reduces transaction costs by replacing formal contracts with norms of reciprocity and reputation, while also serving as an effective social control mechanism through social sanctions. Honesty is proven to be a rational survival strategy for MSME actors to maintain access to community resources. This study recommends strengthening social capital in economic empowerment policies and suggests further field research to measure the impact of digital disruption on trust in rural areas.